Motivasi Mahasiswa UIN Sunan Ampel dalam Pembelajaran Online di Era Pandemi: Tinjauan Perspektif Hamzah B. Uno - Muhammad Thohir; Rizka Dwi Regiyanti; Shofi Nafisah (At-Ta'lim : Media Informasi Pendidikan Islam, 2021)
Abstract: Motivation of UIN Sunan Ampel Students in Online Learning in the Era of a Pandemic: A Review from Hamzah B. Uno’s Perpsective In the era of the Covid-19 pandemic, the education sector underwent many changes. All learning activities, especially in tertiary institutions, are transferred online. These changes have an impact on student learning motivation. This study aims to identify and describe students' learning motivation in online learning during the Covid-19 pandemic. The method uses descriptive with a quantitative approach. The technique used in sampling was purposive sampling with respondents from Islamic Education Management students at Sunan Ampel State Islamic University Surabaya class of 2018. The data collection technique used a Google Form-based questionnaire. The research subjects consisted of 62 students. Data analysis was performed using percentage statistical formulas. The results of the study concluded that student learning motivation in online learning during a pandemic tended to be high, reaching a response of 33.09% strongly agree; 50.54% agree, and 29.12% are neutral. This finding offers new knowledge related to Hamzah B. Uno's theory of motivation and measurement, where during online learning, motivation with various levels of indicators has placed independence as the most important variable.Abstrak: Motivasi Mahasiswa UIN Sunan Ampel dalam Pembelajaran Online di Era Pandemi: Tinjauan Perspektif Hamzah B. UnoDi era pandemi Covid-19 sektor pendidikan mengalami banyak perubahan. Seluruh kegiatan pembelajaran khususnya di perguruan tinggi dialihkan secara daring. Perubahan tersebut memberikan dampak pada motivasi belajar mahasiswa. Penelitian ini bertujuan guna mengetahui dan mendeskiripsikan motivasi belajar mahsiswa dalam pembelajaran online selama pandemi Covid-19. Metode menggunakan deskriptif dengan pendekatan kuantitatif. Teknik yang digunakan dalam pengambilan sampel adalah purposive sampling dengan responden sebagian mahasiswa Manajemen Pendidikan Islam Universitas Islam Negeri Sunan Ampel Surabaya angkatan 2018. Teknik pengumpulan data menggunakan kuisioner berbasis Google Form. Subjek penelitian terdiri dari 62 mahasiswa. Analisis data yang dilakukan dengan menggunakan rumus statistik persentase. Hasil penelitian menyimpulkan bahwa motivasi belajar mahasiswa dalam pembelajaran online selama pandemi cenderung tinggi, mencapai respon 33,09% sangat setuju; 50,54% setuju, dan 29,12% netral. Temuan ini menawarkan pengetahuan baru terkait teori motivasi dan pengukuran Hamzah B. Uno, di mana selama pembelajaran daring berlangsung, motivasi dengan beragam tingkat indikatornya telah menempatkan kemandirian sebagai variabel paling penting.